Powertrain dynamics and control of a two speed dual clutch transmission for electric vehicles. (15th February 2017) - Walker, Paul; Zhu, Bo; Zhang, Nong
Abstract: The purpose of this paper is to demonstrate the application of torque based powertrain control for multi-speed power shifting capable electric vehicles. To do so simulation and experimental studies of the shift transient behaviour of dual clutch transmission equipped electric vehicle powertrains is undertaken. To that end a series of power-on and power-off shift control strategies are then developed for both up and down gear shifts, taking note of the friction load requirements to maintain positive driving load for power-on shifting. A mathematical model of an electric vehicle powertrain is developed including a DC equivalent circuit model for the electric machine and multi-body dynamic model of the powertrain system is then developed and integrated with a hydraulic clutch control system model. Integral control of the powertrain is then performed through simulations on the develop powertrain system model for each of the four shift cases. These simulation results are then replicated on a full scale powertrain test rig. To evaluate the performance of results shift duration and vehicle jerk are used as metrics to demonstrate that the presented strategies are effective for shift control in electric vehicles. Qualitative comparison of both theoretical and experimental results demonstrates reasonable agreement between simulated and experimental outcomes. Highlights: Development of a two speed electric vehicle powertrain model. Presentation of power on and power off shift transient control strategies. Simulations demonstrate effectiveness of control strategy for EVs. Results verified on full scale powertrain test rig.